Clinical Significance of Caseating Granulomas Detected on Transrectal Ultrasound Biopsy of Prostate Gland: The Recommended Management - Salauddin, Syahril Anuar; Sathiyananthan, J.R; Malek, Rohan (IIUM Medical Journal Malaysia, 2021)
Introduction: The histopathological examination (HPE) findings of caseating granulomas from the transrectal ultrasound (TRUS) of prostate biopsy are rare. A high index of suspicion is necessary to diagnose a tuberculosis infection. Here, we present the clinical outcomes of patients and the practical management steps when encounter these findings. Methods: We conducted a retrospective analysis of three cases in a tertiary care centre and reviewed the available literature on the topic. Results: All patients were aged less than 55 years and were considered young adults. One patient presented with neurogenic systemic symptoms, and two patients presented with lower urinary tract symptoms. All patients had abnormal digital rectal examination findings that warranted a TRUS biopsy of the prostate. All biopsies reported caseating granuloma with multinucleated giant cells. Additional investigations led to the diagnosis of tuberculosis infections in two patients, and one patient was diagnosed as having non-specific granulomatous prostatitis. All patients were treated according to their specific diagnosis and recovered fully. Conclusion: The detection of caseating granuloma on prostate biopsy may lead to diagnoses of several conditions, either infective or non-infective in origin. Further investigation is mandatory to provide appropriate treatment.